Young Consumers’ avoidance towards Public Bus Services of urban areas in Bangladesh - Tushi, Tasmia Ekram (Journal of Research in Marketing (ISSN: 2292-9355), 2016)
In this paper; young consumers’ generic avoidance nature towards urban public transportation facilities in Bangladesh has been discussed. From the discussion, four major categories of negative associations regarding public transportation in the urban areas were identified. While three of them have already been explained in the brand avoidance model, another new dimension added to this particular public bus service context was the safety concerns. According to this study result, public bus services are being highly avoided by young urban consumers due to the safety concerns. All the respondents reported some experience or idea about public bus services in the urban city that put them in an unsafe situation. Physical, financial and psychological safety concerns have been experienced by many individuals. Some of them continued traveling with fear of safety concern implanted in mind whereas most of them stopped traveling through public bus services especially during off peak hour or late night hours. The findings are particularly of managerial interest as further transportation management strategies can be crafted to reduce negative customer associations with public transportation facilities.